PERCEPTION OF THE EFFECT OF HUMAN INSECURITY ON AGRICULTURAL ENTERPRISES AMONG RURAL DWELLERS IN SELECTED LOCAL GOVERNMENT AREAS OF OYO STATE, NIGERIA - Mufutau, Rafiu Adeniyi; Adeokun, O. A.; Osunmakinde, M. A.; Awolola, A. A. (Nigerian Journal of Agriculture and Agricultural Technology, 2022)
The study focused on perception of the effect of human insecurity on agricultural enterprises of rural dwellers in selected Local Government Areas of Oyo State, Nigeria. Multistage sampling was used to select 195 rural dwellers from the study area. Data were analyzed using descriptive statistics while Chi-square and Pearson Product Moment Correlation were used as inferential tools. Results showed that, majority (84.10%) of the respondents were married with mean age of, household size and farming experience estimated at 48 years, 7 persons and 13 years, respectively. Major agricultural enterprises engaged in by the respondents were vegetables production (88.21%), arable crop production (69.74%) and marketing of agricultural products%. Also, respondents perceived destruction of crops by animals (79.49%), encroachment of other person’s farmland without permission (68.72%) and clashes between rival cult (52.00%) as causes of human insecurity in the study area. Perception of the effect of human insecurity on agricultural enterprises showed that loss of human lives ranked 1st (= 4.78), human insecurity led to loss of house and properties ranked (= 4.52), human insecurity leads to reduced crop yield/productivity due to theft or burning of farm produce ranked (= 4.48). Among mitigating strategies adopted, provision of small-scale credit facilities was ranked 1st (= 4.21) and provision of health facilities for the stakeholders ranked 2nd (= 4.18) while counseling services for the stakeholders ranked 3rd ( = 3.96). There is a significant relationship between perception of the effect of human insecurity on agricultural enterprises of the rural dwellers and agricultural enterprises practiced by the respondents. The study recommends that, government in collaboration with business owners and companies operating in these crisis prone areas should engage stakeholders (community leaders, youth leaders and other leaders of Community Based Organizations) in a town hall meeting and collectively come up with lasting solutions to human insecurity in the study area.